Students with high skills/giftedness at UFPB: the right to education in the context of inclusive education (Olhar de Professor, 2023)
This article presents a theoretical discussion about High Abilities/Giftedness (HA/GT) and the actions of the Inclusion and Accessibility Commitee (IAC) of the Federal University of Paraiba (UFPB). The issue at hand is the inclusion of students with HA/GT in higher education with the objective of knowing who these people are and what are their needs; the myths that surround them; as well as a discussion about legal principles and the materialization of inclusion at UFPB. This study has a qualitative approach, with bibliographical and documental characteristics, making use of primary sources. The data allows us to state that people with HA/GT still are, in many ways, invisible in educational institutions, highlighting the need to promote propositional actions of inclusion that permeate, initially, through the identification of subjects, the creation of groups/nuclei that can conceive and implement an inclusive academic curriculum, as well as eliminating barriers within the academic sphere.
Keywords: Social inclusion.; Public policy.; University education.; High abilities.